Shape-shifting p-cyclophanes as portals to switching, sensing, delivery and logic operations in water. Issue 6 (1st February 2023) - Yao, Chao-Yi; Lin, Hong-Yu; Daly, Brian; Chen, Ze-Qing; Crory, Hannah S. N.; Gunaratne, H. Q. Nimal; Anslyn, Eric V.; de Silva, A. Prasanna
Abstract : Switchable cyclophanes allow capture/release of guests to control their properties. Abstract : The hybridization state of carbon atoms between phenylene units in p -cyclophanes is shown to control the guest binding properties of these hosts. Dimeric cyclophanes can be shape-switched by redox so that small aromatics can be captured or released. Trimeric cyclophanes perform similar functions on polypyridineRu(ii ) complexes. Controlled capture and release are key to delivery of such cargos. The luminescence and electrochemical signals which are modulated during these processes serve as sensing functions. Some of these modulations are so strong that Boolean logic schemes can be applied. Small-scale serial integration of sequential and combinational logic is seen.